Ontogenetic changes in seminal fluid gene expression and the protein composition of cricket seminal fluid. Issue 2 (11th March 2014) - Simmons, Leigh W.; Beveridge, Maxine; Li, Lie; Tan, Yew‐Foon; Millar, A. Harvey
SUMMARY: The ejaculates of most internally fertilizing species consists of both sperm and seminal fluid proteins. Seminal fluid proteins have been studied largely in relation to their post‐mating effects on female reproductive physiology, and predominantly in genomically well‐characterized species. Seminal fluids can also play important roles in sperm maturation and performance. In the field cricket Teleogryllus oceanicus the viability of ejaculated sperm increases as males age, as does their competitive fertilization success. Here, using quantitative proteomics and quantitative real‐time PCR, we document ontogenetic changes in seminal fluid protein abundance and in seminal fluid gene expression. We identified at least nine proteins that changed in abundance in the seminal fluid of crickets as they aged. Gene expression was quantified for five seminal fluid protein genes, and in four of these gene expression changed as males aged. These ontogenetic changes were associated with a general increase in the size of the male accessory glands. Several of the seminal fluid proteins that we have identified are novel, and some have BLAST matches to proteins implicated in sperm function. Our data suggest that age related changes in competitive fertilization success may be dependent on seminal fluid chemistry.